The graduate [videorecording (DVD)] - Nichols, Mike; Bancroft, Anne, 1931-2005; Hoffman, Dustin, 1937-; Ross, Katharine, 1940-; Daniels, William, 1927-; Hamilton, Murray (MGM Home Entertainment, 2005)
A recent college graduate from an affluent family is seduced by the wife of his father's business partner, then subsequently falls in love with her daughter.